2022
DOI: 10.1155/2022/7643322
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Butyrate Attenuates Diabetic Kidney Disease Partially via Histone Butyrylation Modification

Abstract: Inflammation and fibrosis are the important pathophysiologic processes in diabetic kidney disease (DKD), which is induced by epigenetics, especially histone posttranslational modification (HPTMs). Recent reports highlighted that butyrate, one of the short-chain fatty acids (SCFAs) primarily originated from the fermentation of dietary fiber in the gut, attenuates inflammation and fibrosis in the prevention and treatment of DKD; however, the molecular mechanisms are still unclear. Histone lysine butyrylation (Kb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The enrichment of Hungatella, Escherichia, and Lactobacillus were found in patients with DKD compared to healthy controls, whereas decreased proportions of the genera Butyricicoccus, Lachnospira, Faecalibacterium, and Roseburia were indicated according to the qualitative and quantitative analyses. These four genera are butyrate-producing bacteria (52-54), and have been reported diversified renoprotective effects for DKD in vivo and in vitro, such as improving intestinal barrier function (55), attenuating fibrosis and collagen deposition, inhibiting inflammation (56), and ameliorating TGF-b1-induced fibrogenesis, apoptosis and DNA damage in the diabetic kidney (57). Lactobacillus have been used widely in foods and probiotic products and showed beneficial effects (58), however, upregulated inflammatory cytokines were also significantly increased in Lactobacillus-treated mice, such as tumor necrosis factor-a, IL-6, and IL-1b (59), therefore, the specific role of Lactobacillus in DKD needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…The enrichment of Hungatella, Escherichia, and Lactobacillus were found in patients with DKD compared to healthy controls, whereas decreased proportions of the genera Butyricicoccus, Lachnospira, Faecalibacterium, and Roseburia were indicated according to the qualitative and quantitative analyses. These four genera are butyrate-producing bacteria (52-54), and have been reported diversified renoprotective effects for DKD in vivo and in vitro, such as improving intestinal barrier function (55), attenuating fibrosis and collagen deposition, inhibiting inflammation (56), and ameliorating TGF-b1-induced fibrogenesis, apoptosis and DNA damage in the diabetic kidney (57). Lactobacillus have been used widely in foods and probiotic products and showed beneficial effects (58), however, upregulated inflammatory cytokines were also significantly increased in Lactobacillus-treated mice, such as tumor necrosis factor-a, IL-6, and IL-1b (59), therefore, the specific role of Lactobacillus in DKD needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Butyrate inhibits the expression of renal inflammation and fibrosis genes through p300‐mediated histone Kbu and improves DKD. 557 Other studies have found that crotonylation and 2‐hydroxyisobutyrylation also play a significant role in ESRD. By analyzing crotonylation and 2‐hydroxyisobutyrylation in PBMCs of patients with ESRD, it is speculated that crotonylation and 2‐hydroxyisobutyrylation may affect immune cell numbers and induce immune senescence, which may be due to regulation of the glycolytic/gluconeogenesis pathway and protein processing.…”
Section: Other Scfa Modificationsmentioning
confidence: 97%
“…Inhibition of histone Kbu with the histone modification enzyme p300 inhibitor A485 reversed the anti-inflammatory and anti-fibrosis effects of butyrate. 74 Besides, higher levels of H3K9bu modulate transverse aortic constriction-induced reprogramming of gene expression to inhibit hypertrophic growth of the heart and protect cardiac ejection fraction in mice. 24 Since a high-fat diet has been reported to reduce the H3K9bu levels in the heart, 24 obesity may contribute to the development of CVDs by reducing H3K9bu abundance.…”
Section: Acylations In Cardiovascular Biology and Diseases - An Updat...mentioning
confidence: 99%